3(x+1)+1+2x=2(2x-2)+x

Simple and best practice solution for 3(x+1)+1+2x=2(2x-2)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+1)+1+2x=2(2x-2)+x equation:



3(x+1)+1+2x=2(2x-2)+x
We move all terms to the left:
3(x+1)+1+2x-(2(2x-2)+x)=0
We add all the numbers together, and all the variables
2x+3(x+1)-(2(2x-2)+x)+1=0
We multiply parentheses
2x+3x-(2(2x-2)+x)+3+1=0
We calculate terms in parentheses: -(2(2x-2)+x), so:
2(2x-2)+x
We add all the numbers together, and all the variables
x+2(2x-2)
We multiply parentheses
x+4x-4
We add all the numbers together, and all the variables
5x-4
Back to the equation:
-(5x-4)
We add all the numbers together, and all the variables
5x-(5x-4)+4=0
We get rid of parentheses
5x-5x+4+4=0
We add all the numbers together, and all the variables
8!=0
There is no solution for this equation

See similar equations:

| –2p=p−9 | | (x–3)=5x+2 | | x2(x-7)=4 | | 3c+6=-3c+5 | | 3x+2x+2x-7=91 | | 18k–3=12k+33= | | 15(2.718)^3x=120 | | -12.11x-10.5=75.6-3.5x  | | 28−k=7(k−4) | | -2y+2y^{2}=0 | | 10=5x-3x+6 | | –8d+7=–7d | | -8x-12=-20* | | 3(2-4b)=90 | | 20x+10=-2+22x | | 7.9+1.8z=13 | | -16=5n=-7(-6+-8n)+3 | | w+4+1/2=12 | | 91=3x | | 32/2+6=2x | | 15x+48+10x-18=180 | | 1/4x+10=3/20x-7/10 | | (x-42)=2x | | 16=z+3 | | 3 = n89 | | -9x+11=-7* | | 3z+9-2z-13=4z-22 | | 30=42y-18 | | 2=x+4-6 | | .625x+4=19 | | v2+8=12 | | v2+ 8=12 |

Equations solver categories